Exercise has a Disproportionate Role in the Pathogenesis of Arrhythmogenic Right Ventricular Dysplasia/Cardiomyopathy in Patients Without Desmosomal Mutations - Sawant, Abhishek C. (J Am Heart Assoc, 2014)
BACKGROUND: Exercise is associated with age‐related penetrance and arrhythmic risk in carriers of arrhythmogenic right ventricular dysplasia/cardiomyopathy (ARVD/C)‐associated desmosomal mutations; however, its role in patients without desmosomal mutations (gene‐elusive) is uncertain. This study investigates whether exercise is (1) associated with onset of gene‐elusive ARVD/C and (2) has a differential impact in desmosomal and gene‐elusive patients. METHODS AND RESULTS: Eighty‐two ARVD/C patients (39 desmosomal, all probands) were interviewed about regular physical activity from age 10. Participation in endurance athletics, duration (hours/year), and intensity (MET‐Hours/year) of exercise prior to clinical presentation were compared between patients with desmosomal and gene‐elusive ARVD/C. All gene‐elusive patients were endurance athletes. Gene‐elusive patients were more likely to be endurance athletes (P<0.001) and had done significantly more intense (MET‐Hrs/year) exercise prior to presentation (P<0.001), particularly among cases presenting < age 25 (P=0.027). Family history was less prevalent among gene‐elusive patients (9% versus 40% desmosomal, P<0.001), suggesting a greater environmental influence. Gene‐elusive patients without family history did considerably more intense exercise than other ARVD/C patients (P=0.004). Gene‐elusive patients who had done the most intense (top quartile MET‐Hrs/year) exercise prior to presentation had a younger age of presentation (P=0.025), greater likelihood of meeting ARVD/C structural Task Force Criteria (100% versus 43%, P=0.02), and shorter survival free from a ventricular arrhythmia in follow‐up (P=0.002). CONCLUSIONS: Gene‐elusive, non‐familial ARVD/C is associated with very high intensity exercise suggesting exercise has a disproportionate role in the pathogenesis of these cases. As exercise negatively modifies cardiac structure and promotes arrhythmias, exercise restriction is warranted.